Analysis of the Effect of the English Learning Method on Student’s Learning Interest in Madrasah Aliyah Laboratorium State Islamic University of North Sumatra Medan - Intan Nuriatama; Nuranisa; Nuriana; Sulistina Ratulani; Siti Ismahani; Fajar Aldiansyah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
In this research journal, the author analyzes the interest of Madrasah Aliyah Laboratorium State Islamic University of North Sumatra Medan students in learning English Language in class. The focus of this research is to find some defening factors that faced students in learning English Language. The study is done by taking students randomly from the Madrasah Aliyah Laboratorium State Islamic University of North Sumatra Medan. This study uses a classical and individual approach in collecting qualitative and quantitative data. The data obtained were obtained from the results of student learning exploration in the classroom and conducting interviews with students. The results show that the determinant of increasing or decreasing students interest in learning English in class is determined by the method used by the teacher in learning and the completeness of learning facilities. In connection with the research results obtained, it is suggested that teachers can use learning methods that are preferred by students so that students get a high sense of motivation to learn English in the classroom.